Investigasi prefrensi siswa terhadap aktivitas speaking dan jenis input pada kelas jurusan tata busana - Ella Jeniro Jambak; Widya Syafitri; Irwandi; Eliza (ELP (Journal of English Language Pedagogy), 2026)
Speaking skill is an essential component of English for Specific Purposes (ESP) instruction in vocational education, particularly for Fashion Design students, as it supports effective communication in professional and workplace contexts. This study aims to explore students’ preferences regarding speaking activities and input types in ESP classes. The research employed a descriptive quantitative research design. Data were collected through a close-ended questionnaire administered to 67 students of the Fashion Design major at SMKN 2 Bukittinggi. The collected data were analyzed descriptively using percentage analysis.The findings reveal that role play was the most preferred speaking activity (47%), followed by question-and-answer activities (26%), indicating students’ strong preference for interactive and communicative tasks. In terms of input types, authentic audiovisual materials (39%) were most favored, followed by picture-supported monologues (30%) and vocabulary-supported monologues (27%). Additionally, most students preferred medium-length texts (56%), materials sequenced from easy to difficult (57%), and learning materials accompanied by illustrations or tables (80%).These results suggest that ESP speaking materials for vocational learners should be interactive, multimodal, and contextually relevant. This study provides practical implications for ESP teachers and material developers in designing speaking materials that better address the needs of Fashion Design students in vocational education.